Influence of HTC levels on temperature and stress levels in a leading edge impingement system. (31st January 2019) - Pearce, Robert; Ireland, Peter; Dane, Edwin
Abstract : Accurate analysis of the performance of a turbine blade cooling system is essential to allow the blade life to be safely predicted. The latter is essential as the business model for an engine can be strongly dependent on the duration between engine shop visits. Some recent heat transfer research has focused on increasing heat transfer levels in order to reduce turbine blade metal temperatures, however for engine designers it is the life of the blade, determined in part by the stress levels within it, that are of main concern. This paper uses heat transfer and stress analysis within the same software environment to examine the influence of the HTC levels in different regions of an engine representative leading edge impingement cooling system on both metal temperature and stress levels. The results of these analyses are then combined to show that, with attention to cooling in different regions of the blade, reductions in stress levels of 6% can be achieved in the most highly stressed regions of the blade with achievable alterations in heat transfer levels.